Spekulative Vernunft und die Möglichkeit befreiender Ver-änderung. Hegelianische Perspektiven - Schäfer, Gregor (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2023)
The present paper follows two main interests. Firstly, it argues for a critical understanding of freedom as involved in the complexity of an ongoing, per se conflictive, and contradictory process of liberation and qualitative change. Secondly, this understanding of freedom is brought together with its – systematic – foundations in Hegel’s conception of speculative idealism. As well as freedom hereby is critically articulated against dominant ideologies of freedom, Hegel’s speculative idealism is defended against dominant strands of receptions that reduce the complexity of the entire system. Whilst it is a common strategy of many influential receptions to separate Hegel’s philosophy of objective spirit – as the conception of politically-historically actualized freedom – from its speculative-logical framework and from absolute spirit as the system’s ultimate figure, the paper argues for the inherent connection between these two parts and, by doing so, for the emancipatory core of speculative reason. This setting implies that if, on the contrary, Hegel’s practical philosophy is separated from the speculative-logical framework and from absolute spirit, it loses its critical potential towards existing social-political conditions by being integrated into their hegemony (as expressed in dominant ideologies of freedom). In opposition to such a both hermeneutical and practical integration, the paper claims that speculative reason, by systematically articulating the world as a whole, makes visible, within the existing state of things, a crisis: an unsettling field of conflicts and struggles opening up the possibility of emancipation. Hegel; Absolute Spirit; Crisis; Emancipation; Freedom; Objective Spirit; Speculative Idealism; System; World History.